Moving from a Mechanical Microkeratome to a Femtosecond Laser for LASIK to Correct Astigmatic Patients: Clinical Outcomes of a Retrospective, Consecutive, Comparative Study - Guber, I.; Moetteli, L.; Magnin, L.; Majo, F. (Klinische Monatsblätter für Augenheilkunde, 2013)
Background: To evaluate outcomes after optimized laser in situ keratomileusis (LASIK) for astigmatism correction with flap created by a mechanical microkeratome or a femtosecond laser. Patients and Methods: In this retrospective study, a total of 102 eyes of 71 consecutive patients were enrolled undergoing optimized LASIK treatments using the Allegretto laser system (WaveLight Laser Technologie AG, Erlangen, Germany). A mechanical microkeratome for flap creation was used (One Use, Moria®) in 46 eyes (31 patients, spherical equivalent [SE] −4.44 D ± 2.4) and a femtosecond laser was used (LDV, Ziemer®) in 56 eyes (40 patients, spherical equivalent [SE] −3.07 D ± 3.3). The two groups were matched for inclusion criteria and were operated under similar conditions by the same surgeon. Results: Overall, the preoperative spherical equivalent was −9.5 diopters (D) to +3.37 D; the preoperative manifest astigmatism was between −1.5 D and −3.5 D. At 6 months postoperatively, the mean postoperative uncorrected distance visual acuity (UDVA) was 0.93 ± 0.17 (range 0.4 to 1.2) in the Moria group and 1.0 ± 0.21 (range 0.6 to 1.6) in the Femto group, which was statistically significant (p = 0.003). Comparing the cylinder power there was a statistical difference between the two groups (p = 0.0015). Conclusions: This study shows that the method of flap creation has a significant impact on postoperative astigmatism with a significantly better postoperative UDVA in the Femto group. These findings suggest that the femtosecond laser provides a better platform for LASIK treatment of astigmatism than the commonly used microkeratome.
Keywords: LASIK; Femto-LASIK; microkeratome; femtosecond laser